2019
DOI: 10.2106/jbjs.18.00765
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Corrective Osteotomy for Malunited Fractures of the Upper Extremity Using Patient-Matched Instruments

Abstract: Background: Medical image processing has facilitated simulation of 3-dimensional (3-D) corrective osteotomy, and 3-D rapid prototyping technology has further enabled the manufacturing of patient-matched surgical guides and implants (patient-matched instruments, or PMIs). However, 3-D corrective osteotomy using these technologies has not been the standard procedure. We aimed to prospectively verify the efficacy and safety of PMIs in corrective osteotomy for deformities of the upper extremity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 56 publications
0
38
0
1
Order By: Relevance
“…Concerning the development of the patient-matched plate for the CVD, there were only two studies-one by Omori et al [12] in a cadaveric study and the other by Oka et al [13] in a prospective multicenter study. In these studies, both patient-matched plate designs were made from titanium and placed on the lateral side of the distal humerus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the development of the patient-matched plate for the CVD, there were only two studies-one by Omori et al [12] in a cadaveric study and the other by Oka et al [13] in a prospective multicenter study. In these studies, both patient-matched plate designs were made from titanium and placed on the lateral side of the distal humerus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, three-dimensional (3D) printing technology has been continually developing and become one of the most exciting and fastest growing elds in healthcare due to excellent accuracy that stems from using preoperative computerized tomography (CT) evaluations and advanced computer software; this technology enables personalized treatment and introduces wide-ranging potential uses, including in the clinical application of orthopedic surgery [6]. Regarding the treatment of CVD, previous studies showed that 3D printing technology is bene cial for preoperative planning [7], designing individualized surgical guides [8,9,10], preparing prebent plates with real-sized plastic bone models [11], and printing patientmatched plates [12,13]. However, to the best of our knowledge, the application of 3D printing technology in the treatment of CVD remains limited to designing osteotomy guides for simple techniques, such as lateral closed-wedge osteotomy, and mostly xations with conventional implants.…”
Section: Introductionmentioning
confidence: 99%
“… 44 However, as new PROMs continue to be developed (eg, PROMIS), it is increasingly important to administer simple, efficient instruments that are also appropriately discriminative of outcomes. 37 VAS instruments are the existing gold standard in the evaluation of pain, 7 , 23 , 28 , 38 , 58 and instrument-based advantages in efficiency and simplicity have led researchers to examine VAS instruments in functional disability, 1 hand function and grip, 15 , 29 and general health status and monitoring of symptoms. 13 , 26 The current study suggests that in those with GHOA, the VAS Pain measure outperforms the VAS Function and VAS Strength measures relative to legacy instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The PSP is designed to fit the patient's bone contour optimally; this has the advantage of aligning the bone segments according to the preoperative plan, which may limit tendon ruptures [22], and obviating the need for secondary surgery for plate removal [23] as is common when using standard plates. Preclinical studies [15,20] and initial clinical evaluations [16,24,25] have shown the PSP method to be promising for corrective osteotomy of the distal radius.…”
Section: Introductionmentioning
confidence: 99%